The reality of informality in Peru prior to its bicentennial - Kamichi Miyashiro, Manuel José (2023)
The main objective of this essay is to show the main characteristics of informal employment in Peru before the bicentennial. From the review of various studies in this regard, it can be concluded that informal workers in the country are characterized by low income, low productivity and low educational level. In addition, everything would indicate that informality in Peru is structural, so reforms such as reducing taxes, costs and formalization procedures will only have marginal effects. The solution would be centered mainly on diversifying production, stimulating demand and increasing productivity in smaller production units, which is where most of the informal workers are concentrated.